HAK EKSKLUSIF BANK INDONESIA MENENCABUT IZIN USAHA, PEMBUBARAN BADAN HUKUM DAN LIKUIDASI BANK (PERSPEKTIF HUKUM PERBANKAN NASIONAL) - DEWI ASMAWARDHANI; RINDA PHILONA; NOVITA LISTYANINGRUM; BAIQ NURAINI DWI S.; BAIHAQI SYAKBANI (GANEC SWARA, 2024)
This research is intended to systematically describe and analyze the role of Bank Indonesia authorities as creditors and supervisors and supervisors of banks in maintaining the soundness of banks based on the national banking system, regulating the revocation of business permits, dissolution of business entities and liquidation of banks based on the national banking system and the relevance of granting exclusive rights. to Bank Indonesia to file bankruptcy against the bank based on the Bankruptcy Law and the Banking Law. This type of research is normative juridical, with a statutory and conceptual approach. Based on the research results, it shows: firstly, that Bank Indonesia's authority as a creditor is anticipating financial difficulties faced by a bank within a certain period of time by providing loans with a maximum repayment period of 90 days (3 months). Meanwhile, Bank Indonesia's authority as supervisor and supervisor is aimed at improving the performance of a bank which is determined on the basis of asset quality, management quality, liquidity, profitability and solvency as an effort to increase public confidence in banks. Second; One of the recommendations from Bank Indonesia for one of the banks which, based on Bank Indonesia's assessment, is difficult to save is to revoke the business license, disband the business entity and liquidate the bank. Third: Although based on Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations, it is determined that a bank's bankruptcy statement can only be submitted by Bank Indonesia, but because operationally and institutionally banks have different characteristics from other business entities, the implementation bankruptcy of a bank becomes ineffective, especially if it is linked to the principle of Lex Specialis Derogat Lex Generalis